Nicotine induces neutrophil extracellular traps. Issue 5 (16th June 2016) - Hosseinzadeh, Ava; Thompson, Paul R; Segal, Brahm H; Urban, Constantin F
Abstract : Nicotine induces neutrophils to release DNA traps via activation of Akt, but independently of NADPH oxidase. Abstract: NETs serve to ensnare and kill microbial pathogens. However, NETs can at the same time contribute to tissue damage and excessive inflammation. Nicotine is a major toxic agent and has been associated with exacerbated inflammatory diseases. The current study aimed at investigating the role of nicotine, the addictive component of tobacco and electronic cigarettes, on triggering NET formation. We report that nicotine induces neutrophils to release NETs in a dose-dependent manner. Nicotine-induced NET formation is mediated via nicotine acetylcholine receptors, depends on Akt and PAD4 activation, but is Nox2-independent, as demonstrated by pharmacological inhibition of Nox2 and by use of Nox2-deficient mouse neutrophils. These findings demonstrate that nicotine induces NETs, which may in turn contribute to smoking-related diseases.